2012
DOI: 10.1093/czoolo/58.2.250
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance cues in freshwater prey fishes: Does urea function as an ‘early warning cue’ in juvenile convict cichlids and rainbow trout?

Abstract: Freshwater vertebrate and invertebrate prey species commonly rely on chemosensory information, including non-injury released disturbance cues, to assess local predation threats. We conducted laboratory studies to (1) determine if urea can function as a disturbance cue in juvenile convict cichlids and rainbow trout and (2) determine if the background level of urea influences the behavioral response to a subsequent pulse of urea (‘background noise’ hypothesis). In the first series of trials, juvenile cichlids an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…After passing the model through the tank, we waited 60 s and softly mixed the water around the tank and removed 125 mL of tank water to be used as a disturbance cue. This procedure has previously been used to successfully collect disturbance cues (Vavrek and Brown 2009;Brown et al 2012). We collected all cues immediately before the experiment and used them within an hour of collection.…”
Section: Stimulus Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…After passing the model through the tank, we waited 60 s and softly mixed the water around the tank and removed 125 mL of tank water to be used as a disturbance cue. This procedure has previously been used to successfully collect disturbance cues (Vavrek and Brown 2009;Brown et al 2012). We collected all cues immediately before the experiment and used them within an hour of collection.…”
Section: Stimulus Preparationmentioning
confidence: 99%
“…Alarm cues are reliable and honest indicators of risk (Chivers et al 2012) and can elicit dramatic short-term increases in predator avoidance behaviour (Ferrari et al 2010;Brown et al 2011;Chivers et al 2012). Disturbance cues are argued to be metabolic by-products, released in the urine or across the gill epithelium (Kiesecker et al 1999;Vavrek et al 2008;Brown et al 2012) by aquatic vertebrates when stressed or disturbed (Wisenden et al 1995;Kiesecker et al 1999;Abreu et al 2016). When detected by nearby conspecific and heterospecific prey, disturbance cues may function as an "earlywarning" cue of nearby predation threats (Wisenden et al 1995;Kiesecker et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In fish, urine pulses are used to release mating pheromones (Sorensen & Stacey, ; Stacey, Chojnacki, Narayanan, Cole, & Murphy, ), advertise dominance (Almeida et al., ; Bayani, Taborsky, & Frommen, ; Maruska & Fernald, ), differentiate kin (Moore, Ives, & Kell, ) and, presumably, familiar individuals as well (Ward, ). Disturbance cues in fishes likely involve urea (Brown, Jackson, Malka, Jacques, & Couturier, ), as supported by the fact that fish perceive the presence and intensity of heterospecific disturbance cues, but not the number of individuals (Goldman, Singh, Demers, Feyten, & Brown, ; Vavrek & Brown, ).…”
Section: Introductionmentioning
confidence: 99%
“…In aquatic systems chemical cues are a principal source of information ( DeBose & Nevitt, 2008 ; Ferrari, Wisenden & Chivers, 2010 ). Prey increase anti-predator behaviors in response to the chemical cues of predators (e.g., kairomones Ferrari, Wisenden & Chivers, 2010 ), as well as the chemical cues released by prey that have been injured by predators (e.g., damage-released alarm cues, Mathis, Chivers & Smith, 1993 ; Harvey & Brown, 2004 ; Chivers, Brown & Ferrari, 2012 ; Lönnstedt, McCormick & Chivers, 2012 ), and by prey that have been disturbed or stressed by predators, without being injured or consumed (e.g., disturbance cues, Chivers, Brown & Smith, 1996 ; Vavrek et al, 2008 ; Vavrek & Brown, 2009 ; Ferrari, Wisenden & Chivers, 2010 ; Brown et al, 2012 ). By responding to the chemical cues of heterospecifics and conspecifics, about the presence of predators, prey have increased chances of survival during encounters with predators ( Mirza & Chivers, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Disturbance cues exist in a variety of systems, including invertebrates, amphibians, and freshwater fish ( Hazlett, 1990 ; Wisenden, Chivers & Smith, 1995 ; Kiesecker et al, 1999 ; Bryer, Mirza & Chivers, 2001 ; Mirza & Chivers, 2002 ; Jordão, 2004 ; Brown et al, 2012 ). It has been suggested that nitrogenous compounds in urine, and respiratory byproducts could act as disturbance cues ( Hazlett, 1990 ; Kiesecker et al, 1999 ; Vavrek & Brown, 2009 ; Brown et al, 2012 ). One potential disturbance cue that has received less research attention is the stress hormone cortisol ( Olivotto et al, 2002 ; Vavrek & Brown, 2009 ), the principal glucocorticoid in teleost fish ( Brown, Gardner & Braithwaite, 2005 ).…”
Section: Introductionmentioning
confidence: 99%